LAURENCE STERNE, MACHADO DE ASSIS E O ATO DA LEITURA: A PALAVRA LITERÁRIA COMO EXPERIÊNCIA DO FORA - Trigo, Aline Candido [UNESP]; Nogueira, Nícea Helena De Almeida (Universidade de São Paulo - Faculdade de Filosofia, Letras e Ciências Humanas, 2022)
This article analyzes Tristram Shandy (1759-1767), by Laurence Sterne, and The Posthumous Memoirs of Brás Cubas (1881), by Machado de Assis, considering the mirroring they present of the reader as a character who updates the sparks of meaning in that space of the outside language, based on the concept of Maurice Blanchot. The narrators Brás Cubas and Tristram Shandy refrain from giving full descriptions of events and characters so as not to tarnish the literary experience of their readers. The perspective of both is at the heart of what configures the literary experience: it is an experience that takes place in the space outside the word. Reading literature implies constantly lifting your eyes from the pages and diving into other dimensions of meanings.

Este artigo analisa Tristram Shandy (1759-1767), de Laurence Sterne, e Memórias póstumas de Brás Cubas (1881), de Machado de Assis, a partir do espelhamento que apresentam do leitor enquanto personagem que atualiza as faíscas de sentido nesse espaço do fora da linguagem, a partir do conceito de Maurice Blanchot. Os narradores Brás Cubas e Tristram Shandy se eximem de dar descrições completas de eventos e personagens para não macular a experiência literária de seus leitores. A perspectiva de ambos está no cerne do que configura essa experiência: ela se dá no espaço externo à palavra. Ler literatura implica levantar os olhos das páginas e mergulhar em outras dimensões das significações.
LAURENCE STERNE, MACHADO DE ASSIS, AND THE ACT OF READING: THE LITERARY WORD AS EXPERIENCE OF THE OUTSIDE
Keywords: Tristram Shandy; The Posthumous Memoirs of Brás Cubas; literary reading; experience of the outside; Tristram Shandy; Memórias póstumas de Brás Cubas; leitura literária; experiência do fora